PEMANFAATAN KOTORAN KAMBING MENJADI PUPUK ORGANIK PADAT - Siti Alfiatur Rohmaniah; Awawin Mustana Rohmah; Makhrus Afif; Maftuh Nur Muhammad (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2021)
Keting village, Kedalon hamlet is a village that still has a lot of rice fields and livestock. However, many people are still not using animal manure (livestock) to be used as fertilizer in the rice fields. In this case, the community still uses chemical fertilizers and allows the manure from the farm to be wasted for nothing. The purpose of this community service is to manage goat manure into solid organic fertilizer or manure to replace chemical fertilizers in Kedalon Hamlet. The method used in this activity is socialization and the practice of making fertilizer. The results of the service are products in the form of solid organic fertilizers derived from goat manure, so that comunity can use these fertilizers to replace chemical fertilizers.